226k views
3 votes
Select the correct answer. Which function defines ( - 9)(r) ? f(s) = V + 11 g(t) = 5+ 1 A. + 16 + 6 ( - 3)(x) = V - B. ( - )(r) = VI c. (- 9)() = V + D. (- 9)(x) = 1 + 16 1 6 Reset

Select the correct answer. Which function defines ( - 9)(r) ? f(s) = V + 11 g(t) = 5+ 1 A-example-1
User Beowulf
by
5.2k points

1 Answer

4 votes

Given:


\begin{gathered} f(x)=\sqrt[]{(x)/(8)}+11 \\ g(x)=5+(2)/(x) \end{gathered}

Therefore,


\begin{gathered} (f-g)(x)=f(x)-g(x) \\ \text{ =}\sqrt[]{(x)/(8)}+11-5-(2)/(x)=\sqrt[]{(x)/(8)}+6-(2)/(x) \end{gathered}

Correct option is B.

User Jpmorris
by
6.5k points